Clinical Use of New Video-Endoscopes (EVIS 100 and 200) - Niwa, H.; Kawaguchi, A.; Miyahara, T.; Koyama, H. (Endoscopy, 1992)
The authors report on their clinical experience with two new videoendoscopes developed in cooperation with Olympus Co. One of them is an instantaneous image method videoendoscope (EVIS 100), the other produces sequential images (EVIS 200). EVIS 100 is as compact as a fiberscope; EVIS 200 has the special advantages of electronic magification, the use of infrared rays and image display of hemoglobin concentration in the tissue. In clinical application in 245 patients examined with EVIS 100 and 30 cases with EVIS 200, both instruments were found to be satisfactory in terms of daily use; EVIS 200 could be applied in further endoscopic research. In our opinion videoendoscopes will replace conventional fiberscopes in the future.